La visión espaciotemporal en Antonio Muñoz Molina y Javier Tomeo - Eduard Krč (Études romanes de Brno, 2013)
The author makes a detailed comparison of the temporal and spacial elements in the literary work of two well-known contemporary Spanish novelists, Antonio Muñoz Molina and Javier Tomeo. Tomeo develops his artistic compositions within a short time period and in a space reflecting mainly dark and complicated milie, while Muñoz Molina looks for more ambivalent and open places. He also tries to link up personal reflections with the civil postwar epoch in Spain, combining masterly the present and the past.